HEAT TRANSFER CHARACTERISTIC OF VERTICAL COOLING USING SYNTHETIC JET - SH ABDUL NASIR, SH MOHD FIRDAUS; ISMAIL, HAZIMI; MOHD ZAMRI, MUHAMMAD SALEHUDDIN; ABD MANAP, MUHAMMAD FARIS; YUSOFF, MOHD HUZAIFAH (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT - Advancements in technology have resulted in a rise in heat flow within electrical devices. Electronic devices that overheat can break down and experience thermal failure. One cooling method that may be able to prevent electronic overheating is a synthetic jet. This study examined the cooling efficiency and optimal performance characteristics of a synthetic jet cooling device using a vertical cooling approach. The experiment utilized a synthetic jet with varying nozzle sizes (diameters of 2 mm, 4mm, 6 mm, 8 mm, and 10 mm), volume cavities (depths of 1 mm, 2 mm, 3 mm, 4 mm, and 5 mm), and distances between the heater and synthetic jet (distances of 10 mm, 20 mm, 30 mm, 40 mm, 50 mm, 60 mm, and 70 mm). The synthetic jet was held at a consistent frequency of 500 Hz, while the heater, which acted as the processor for the electrical device, was set to a constant temperature of 70 ° C. The experimental results indicate that a nozzle diameter of 2 mm yields the best cooling effects compared to other nozzle diameters tested. The optimum distance found from the experiment is 30 mm. The lowest average surface temperature is 40.53°C with a heat transfer coefficient 98.99W/m2.°K with a Nusselt number of 7.56.